The Influence Of Differences In Judges' Opinions On Legal Certainty In Deciding A Case - Claudia, Jean; Firmansyah, Hery (RechtIdee, 2025)
This study examines the influence of differences of opinion among judges on legal certainty in court decisions. In judicial practice, differences of opinion between judges often arise and have the potential to affect consistency and legal certainty, which are one of the main pillars of the legal system. The research method used is qualitative with a juridical-normative approach, utilizing analysis of relevant laws and legal literature. The results of the study indicate that differences of opinion among judges can cause legal uncertainty if not managed properly, thus impacting the credibility of the judicial institution and public trust in the judge's decision. Therefore, it is important to develop clear mechanisms and standards for handling differences of opinion among judges to maintain legal certainty in the judicial system.